Effects of temperature on the CFRP confining pressure in strengthened concrete columns - Muhammad Rashid, Raizal Saifulnaz; M. H., Azmi; Aboutaha, Riyad; P., Alireza (2015)
Carbon Fiber Reinforcement Polymer (CFRP) is a high strength carbon fiber which is bound by a resin such as epoxy, polyester, vinyl ester or nylon to form an extra hard matrix which is approximately 10 times harder than steel, saliently has a light weight and surprisingly without being impacted by any corrosion effect. Due to these beneficial properties FRP nowadays is one of the most used materials in structural engineering for strengthening of structures and grabbed the attention of industries such as car industries, aviation and sports equipment as well. The main objective of this project is finding the FRP confined column behaviour in the temperature under the axial loading. Objectives of this research are to investigate the force-Displacement graph of each group of non-wrapped, 1-layer, 2-layer and 3-layer FRP wrapped under the axial loading in different temperatures less than 100°C. (32°C , 60°C , 70°C , 80°C), to investigate the change in ultimate force (stress) in samples in the different temperature under axial loading and to compare the changes in ultimate force and displacement under the axial loading in different temperatures. From the output of this research, it can be observed that the CFRP layered specimen has exhibited lower strength reduction in compared with non-layered columns with the increased of the temperature. This also applied to the number of CFRP layers on the column where lower reduction of final strength with the increase of the number of layers.